EGCG inhibits the inflammation and senescence inducing properties of MDA-MB-231 triple-negative breast cancer (TNBC) cells-derived extracellular vesicles in human adipose-derived mesenchymal stem cells - Narjara Gonzalez Suarez; Yuniel Fernandez-Marrero; Mathieu P. A. Hébert; Marie-Eve Roy; Luc H. Boudreau; Borhane Annabi (Cancer Cell International, 2023)
Abstract Background Triple-negative breast cancer (TNBC) cells’ secretome can induce a pro-inflammatory phenotype in human adipose-derived mesenchymal stem cells (hADMSC). This can be prevented by the green tea polyphenol epigallocatechin-3-gallate (EGCG). The impact of EGCG on the paracrine regulation that the extracellular vesicles (EVs) specifically exert within the TNBC secretome remains unknown. Methods EVs were obtained from a TNBC-derived serum-starved MDA-MB-231 cell model treated or not with EGCG under normoxic or hypoxic (< 1% O2) culture conditions. RNA-Seq analysis was used to assess the EVs’ genetic content. The modulation of inflammatory and senescence markers in hADMSC was evaluated by RT-qPCR using cDNA arrays and validated by immunoblotting. A protein profiler phospho-kinase array was used to explore signaling pathways. Results While hypoxic culture conditions did not significantly alter the genetic content of MDA-MB-231-secreted EVs, the addition of EGCG significantly modified EVs genetic material at low oxygen tension. Gene expression of cancer-associated adipocyte pro-inflammatory markers CXCL8, CCL2 and IL-1β was increased in hADMSC treated with EVs. Concomitantly, EVs isolated from MDA-MB-231 treated with EGCG (EGCG-EVs) downregulated CCL2 and IL-1β, while inducing higher expression of CXCL8 and IL-6 levels. EVs activated CHK-2, c-Jun, AKT and GSK-3β signaling pathways in hADMSC, whereas EGCG-EVs specifically reduced the latter two as well as the serum starvation-induced senescence markers p21 and β-galactosidase. Finally, the mitochondrial content within the TNBC cells-derived EVs was found reduced upon EGCG treatment. Conclusion This proof of concept study demonstrates that the chemopreventive properties of diet-derived polyphenols may efficiently target the paracrine regulation that TNBC cells could exert upon their surrounding adipose tissue microenvironment.